2018
DOI: 10.3390/su10072421
|View full text |Cite
|
Sign up to set email alerts
|

Can China’s Carbon Emissions Trading Rights Mechanism Transform its Manufacturing Industry? Based on the Perspective of Enterprise Behavior

Abstract: The pilot policy of carbon emissions trading rights covers six heavy pollution industries in the manufacturing industry and has achieved considerable emission reductions. Based on enterprise behavior, this study analyzes the impact of the carbon emissions trading rights pilot policy on the productivity of manufacturing enterprises. In addition, we examine whether the pilot policy can aid in the transformation and upgrading of China's manufacturing industry. Furthermore, we examine the influence of carbon emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Dong et al (2019) compared the effect of pilot ETS with the command-andcontrol regime in the "Eleventh Five-year Plan" (2006)(2007)(2008)(2009)(2010) and noted that emission reduction achieved during this period was contributed by tight control measures that included throttling of power supply. Dai et al (2018) analyzed firm-level data in 2011-2015 and found remnants of this behavior, in that the productivity of state-owned enterprises was reduced and ETS trading volume was not as high as anticipated. They concluded that state-owned enterprises bore the burden of compliance cost without effectuating competitiveness boosting measures in the early phase of pilot ETS.…”
Section: Impact On Firmsmentioning
confidence: 95%
“…Dong et al (2019) compared the effect of pilot ETS with the command-andcontrol regime in the "Eleventh Five-year Plan" (2006)(2007)(2008)(2009)(2010) and noted that emission reduction achieved during this period was contributed by tight control measures that included throttling of power supply. Dai et al (2018) analyzed firm-level data in 2011-2015 and found remnants of this behavior, in that the productivity of state-owned enterprises was reduced and ETS trading volume was not as high as anticipated. They concluded that state-owned enterprises bore the burden of compliance cost without effectuating competitiveness boosting measures in the early phase of pilot ETS.…”
Section: Impact On Firmsmentioning
confidence: 95%
“…Yin et al [35] show that the EU carbon trading price and air quality index have a direct effect on China's carbon trading price. Dai et al [36] find that China's Carbon emissions trading rights mechanism does not transform its manufacturing industry, based on the Perspective of Enterprise Behavior. Our results provide theoretical evidence for government, enterprises, financial organizations, and investors to determine a risk aversion strategy and maintain the stable development of the carbon financial market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Equation (7) represents the objectives of maximizing employment and minimizing the total pollution control cost, respectively. Equations (8) to (9) are the constraints of the double-objective optimization model. Equation (8) means that the total pollutant emission minus the total pollutant abatement quantity in a certain region shall not exceed the environmental capacity of the region (i.e.…”
Section: Classification Of Regions Into Sellers and Buyers Of Emissiomentioning
confidence: 99%
“…Various countries take different measures to control air pollution; they include direct control, environment protection tax [6,7], emission trading [8][9][10], and environmental protection technologies such as recycling and reuse [11,12]. Of these options, air pollution control based on emission rights trading has attracted more attention [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation